O trabalho do(a) assitente social nos CREAS e o atendimento às medidas socioeducativas - Gouveia, Nathália de Medeiros (2016)
The present dissertation aims at analysing the process of adolescents attendancy who take part in the Adolescent Social Protection Service, taking into consideration the socio educating measures into the open prison condition offered by CREAS(Centro de Referência Especializado da Assistência Social/ Social Assistance Specialized Reference Centre). The study has also tried to identify what are the limits and challenges required to the work of a Social Assistant. The interest in developing the current analytical proposal has been manifested, firstly through the professional experiences lived as a Coordinator in Regional CREAS-PB, and secondly by the nowadays importance of this study, considering its social relevance to our society. A question itself which may also undergo threats and going-backs, with the possible approval of the penal majority reduction proposal. For this, it has been drawn an outline of the quantitative and qualitative research, making the choice for an exploratory study using the resource of bibliographical research. The field research has been accomplished within the month of June of the current year, together with the 10 (ten) Social Assistants who make the multi-professional teams of the 4 (Four) CREAS in the city of João Pessoa/PB. The study presents a short summary of the historical process of the Children and Adolescents Rights Constitution of Brazil, taking into account the Policies of Social Assistance and of Children and Adolescent Human Rights. It also points out, an accurate scenery of the Socio Educative Service Policy, approaching the current regulamentations concerning to adolescent social protection who are in conflict with the law, through the ECA(Estatuto da Criança e do Adolescente/ Children and Adolescence Statute)-SINASE(Sistema Nacional de Atendimento Socioeducativo/ Nacional System of Socio Educating Attendance)- SUAS(Sistema Único de Assistência Social/ Social Assistance System), focusing in the interface between SINASE and SUAS. The last chapter of this study shows data of the field research, and it has been concluded that, during neoliberal times, where children and adolescent rights had been denied, the scenery of Adolescent Socio Educative Service Promotion, the one which considers the socio educative measures in an open prision condition in the city of João Pessoa, presents limits and challenges which questions this same effectiveness of the socio educative measures. It is necessary that, the city, as well as its managements, define mechanisms to the establishment of the SINASE Law, in order to make possible that, adolescents in conflict with both the law and their families, may reconstruct their lives project and may overcome the situations of both personal and social risk.